Reintegrasi Wanita Sebagai Perhiasan Dunia Dalam Akun Youtube Dzulqarnain ms - Wildan Sholeh, Adam; Syamsul Huda, Muhammad; Abidin Zamroni, Zainul (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2024)
Culture that is patriarchal in nature is still developing in society, where the social construct that applies in society always places women second to men, the role of women in the household is limited only in the domestic sphere. Analysis of the interpretation of the Koran surah Ali Imran verse 14 in various classic commentary books places women only as objects that can only seduce men, but cannot be seduced by men, women are considered the source of all beauty that can lead men to actions that misleading. So that it is suspected of causing a biased interpretation of gender. This construction was also conveyed by DzulqarnainMS on his YouTube account which has been watched by approximately 44 million viewers. The theory of Qiraah mub is to offer a new perspective in interpreting the Koran. The offer is to link the roles of men and women in providing significant implications for the meaning of the moral message conveyed by the Koran. Therefore, the question in this research is how to understand the meaning of women as world jewelry conveyed by the DzulkarnainMS account when viewed from the perspective of qiraah mublain. This study is a literature study with a qualitative approach. The result of this study is that the interpretation conveyed by the dzulqarnain account is considered too textual and ignores the position of women who are only used as objects, while men are the subjects discussed in the Qur'an.